DATA PRIVACY IN E-COMMERCE BUSINESS: CHALLENGES AND LEGAL SOLUTIONS - Gunawan Widjaja; Hotmaria Hertawaty Sijabat (Jurnal Komunikasi, 2025)
This study discusses the challenges and legal solutions related to data privacy in e- commerce businesses, which is becoming increasingly important as the volume of online transactions increases. Consumer data privacy faces significant risks due to cybersecurity threats and the complexity of cross-jurisdictional regulations. To overcome these challenges, a series of legal solutions are needed, including strengthening privacy regulations, increasing corporate transparency in data use, and educating consumers and businesses. The implementation of regulations such as GDPR and CCPA shows important progress in the protection of personal data, but continuous efforts are needed to maintain consumer trust and ensure effective compliance worldwide.